(untitled) (Sambahak: Human Rights Journal, 2025)
Climate change impacts on the livelihood of people. Climate change can be studied in constitutional and legal context. This paper focuses on the rights provisioned in the constitution and law for ensuring the climate justice. The challenges of Climate change in Nepal is highlighted with special focus on the constitutional provisions of fundamental rights, directive principles and state policies. This paper addresses the questions about the role of law for climate justice, constitutional provisions about the green transition and the role of Supreme Court in this process. The conclusion of this paper rests on law-science inter face that plays role in securing justice to people. This paper helps understand the sustainable development as provided in The Constitution of Nepal. It even highlights the need of the international environmental courts to address the accountability gaps witnessed in international climate negotiations especially in areas of climate finance, loss and damage and tardiness in transitioning to carbon neutral economy. The gaps also create obstacles in securing climate justice at the domestic level. So the policy makers at the domestic level need to address for safeguarding the environmental safety for all the generations.